Aquaporin 7 involved in GINSENOSIDE-RB1-mediated anti-obesity via peroxisome proliferator-activated receptor gamma pathway - Rong Guo; Lei Wang; Xianqin Zeng; Minghao Liu; Peng Zhou; Huixia Lu; Huili Lin; Mei Dong (Nutrition & Metabolism, 2020)
Abstract Background Obesity, characterized by the excessive accumulation of triglycerides in adipocytes and their decreased excretion from adipocytes, is closely related to various health problems. Ginsenoside Rb1 (Rb1), the most active component of the traditional Chinese medicine ginseng, has been reported to have positive effects on lipid metabolism. The aim of the present study was to determine the protective effects of Rb1 on glycolipid metabolism under obesity conditions and its mechanisms and to reveal the signaling pathways involved. Methods In our study, male C57BL/6 mice with obesity induced by a high-fat diet (HFD) and mature 3 T3-L1 adipocytes were used to investigate the role of Rb1 in lipid accumulation and explore its possible molecular mechanism in vivo and in vitro, respectively. Results Rb1 reduced the body weight, fat mass, adipocytes size and serum free fatty acid (FFA) concentration of obese mice. In differentiated 3 T3-L1 adipocytes, Rb1 reduced the accumulation of lipid droplets and stimulated output of triglycerides. Additionally, the expression of peroxisome proliferator-activated receptor gamma (PPARγ), phosphorylated PPARγ (Ser112) and aquaporin 7 (AQP7) was upregulated in adipocytes and adipose tissues upon Rb1 treatment. However, intervention of GW9662, PPARγ antagonist, attenuated Rb1-mediated effects on glycolipid metabolism and AQP7 levels. Conclusions These data indicated that Rb1 reduced body weight and improved glycolipid metabolism by upregulating PPARγ and AQP7 protein levels. Our study indicated a potential role for Rb1 in the prevention and treatment of obesity.